LOYIHAGA ASOSLANGAN O‘QITISH TEXNOLOGIYASI BO‘LAJAK O‘QITUVCHILARDA KREATIV TAFAKKURNI RIVOJLANTIRUVCHI ASOSIY VOSITA SIFATIDA - Sulaymanova, D.N. (SCIENCE and SOCIETY, 2024)
This article analyzes the project, the essence of project-based learning technology, its importance in the educational process, its advantages and disadvantages based on scientific sources. Professional activities, such as enhancing the educational activities of future teachers, adapting it to individual characteristics, developing cognitive capabilities, abilities, interests, creativity, creativity, inner freedom, embodying the meaning of the subject of one’s life through project activities. training, the formation of the necessary qualities is described.